Mixed model-based eQTL analysis reveals lncRNAs associated with regulation of genes involved in sex determination and spermatogenesis: The key to understanding human gender imbalance. (August 2022) - An, Yeeun; Lee, Chaeyoung
Abstract: Background: An imbalance in the prenatal sex ratio in humans may be due to several factors affecting sperm physiology, including genetic features. In this study, we conducted a transcriptome-wide analysis of expression quantitative trait loci (eQTLs) to identify target genes associated with previously described QTLs associated with gender imbalance. Methods: A mixed model explaining polygenic effects by genomic covariance among individuals was used to identify the eQTLs using gene expression and genotype data from 462 European/African individuals. Results: Eight eGenes were associated with four QTLs ( P < 4.00 × 10 -5 ), with strong associations found ( P < 4.00 × 10 -8 ) between rs2485007 and eGenes ANKRD26P3 ( P = 3.40 × 10 -9 ) and LINC00421 ( P = 1.35 × 10 -9 ). ANKRD26P3 and LINC00421 are both lncRNAs associated with the control of testis-dominant genes PELP1, TAF15, NANOG, TEX14, TCF3, ZNF433, ZNF555, TEX37, FATE1, TCP11, and CYLC2 and Y-linked genes SRY and ZFY, as well as several genes with roles in spermatogenesis ( ODF1, SPATC1, SPATA3, SPATA31E1, SPERT, SPATA16, MOSPD1, SPATA24, and SPO11 ) and sex determination (SOX family genes). Conclusions: The above eGenes contribute directly or indirectly to gene regulation for sex determination and spermatogenesis, thereby serving as important functional clues for gender-biased selection. Graphical Abstract: ga1 Highlights: Genetic factors for sperm activity may cause human prenatal sex ratio imbalance. Transcriptome-wide eQTL analyses identified 8 eGenes for sex imbalance. Most significant eGenes encode lncRNAs, ANKRD26P3 and LINC00421. The lncRNAs target genes involved in sex determination and spermatogenesis genes.